(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
The presence of a foreign body in the nose is a relatively uncommon occurrence. Many unusual foreign bodies in the nose have been reported in the literature. Other than the common foreign bodies, some uncommon things have made interest like fish hook, anterior nasal pack, door handle, metal hooks and eyes, umbrella springs and coins also reported. A case of anterior nasal pack also reported and very interesting for several reasons. To the best of our knowledge, the nasal packing in this case is the largest foreign body left in situ. But here a case of lost nasal splint which was kept after septoplasy operation for prolonged time has been discussed. A 32 years old man had this splint in his left nasal cavity for 9 years and had been suffering from persistent nasal discharge for this time. He was treated conservatively by many ENT specialists but had no improved. Afterwards he had undergone surgery and this plastic splint identified and removed. DOI: http://dx.doi.org/10.3329/bjo.v20i2.22027 Bangladesh J Otorhinolaryngol; October 2014; 20(2): 102-105